How Counselling Services Foster Emotional Intelligence among University Students: Evidence from a Mixed-Methods Study in an Islamic Higher Education Context - Anwar Fuadi; Walton Wider; Zulfadli Zulfadli; Anita Ariani (Universitas PGRI Yogyakarta, 2026)
Emotional intelligence (EI) is a key competency supporting students’ psychological well-being, academic engagement, and interpersonal functioning in higher education. However, most EI intervention studies rely on Western-based models and offer limited explanations of how cultural and spiritual values shape EI development. Addressing this gap, the present study examines the effectiveness of an Islamic EI-oriented counseling framework that integrates Islamic spiritual values into conventional EI models. This framework complements existing EI dimensions by embedding values such as sabr (patience), tawakal (trust in God), and self-reflection as mechanisms that strengthen emotional awareness, regulation, and empathy. Using a mixed-methods sequential explanatory design, quantitative data were collected from 123 students at an Islamic university in Indonesia through a one-group pretest-posttest design, followed by qualitative interviews with students and counselors. Paired-sample t-test results revealed a statistically significant increase in EI scores after the intervention (p < 0.001) with an exceptionally large effect size (Cohen’s d = 2.68), indicating a substantial and practically meaningful impact. Qualitative findings further elucidate the mechanism of change, showing that Islamic spiritual meaning-making functions as a catalyst for sustained emotional regulation, empathy, and prosocial behavior. Theoretically, these findings challenge assumptions about the universality of Western EI models and demonstrate the importance of culturally and spiritually grounded counseling frameworks for fostering deep, transformative EI development in higher education contexts. Keywords: emotional intelligence, counseling services, higher education, mixed methods, islamic education